Effects of Ascorbic Acid on Rectal Temperature Fluctuations in Indigenous Turkeys During the Hot-Dry Season - Adenkola, A.Y.; Ayo, J.O. (International Journal of Poultry Science, 2009)
Experiments were performed on 40 indigenous turkeys with the aim of investigating, fluctuations in their rectal temperature (RT) and the effect of ascorbic acid (AA) on during the hot-dry season. Twenty turkeys which served as experimental birds were administered AA orally at the dose of 52 mg kg-1, while the remaining 20 turkeys which served as control were given ordinary water. Measurements of RT were taken for 3 days, one week apart and every hour from 06:00-19:00 h. The results showed that RT values in both experimental and control turkeys significantly (p